2021
DOI: 10.1177/19400829211028127
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Bees and Livestock: Pastoralist Knowledge, Perceptions and Implications for Pollinator Conservation in Rangelands, Northern Tanzania

Abstract: Insect pollinators provide numerous ecosystem services that support other living organisms. While pollinators play a large role in cropping systems, little is known about their presence and function in rangeland ecosystems, which have recently become fragmented and overexploited at an extraordinary rate. We assessed local Maasai knowledge on insect pollinators and how pollinators affect livelihood diversification in Simanjiro rangelands, Tanzania. Through questionnaires, key informant interviews, focus group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(97 reference statements)
2
8
0
Order By: Relevance
“…They also affirmed that the loss of bee-pollinators from local systems would likely harm the environment. This is not different from other studies conducted in Tanzania by Elisante et al (2019), Mpondo et al (2021), andSawe et al (2020), which reported almost similar findings. Additionally, planting flowering trees and wild flowers in the field for bees to forage, reducing pesticide use on farms, and allocating some uncultivated areas to attract A. mellifera and other pollinator insects were perceived by local people as important conservation initiatives.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…They also affirmed that the loss of bee-pollinators from local systems would likely harm the environment. This is not different from other studies conducted in Tanzania by Elisante et al (2019), Mpondo et al (2021), andSawe et al (2020), which reported almost similar findings. Additionally, planting flowering trees and wild flowers in the field for bees to forage, reducing pesticide use on farms, and allocating some uncultivated areas to attract A. mellifera and other pollinator insects were perceived by local people as important conservation initiatives.…”
Section: Discussionsupporting
confidence: 62%
“…However, previous studies are also reporting that the decline of bees may be influenced by the limited knowledge and negative perceptions of people towards bees (Burns et al, 2021;Marques et al, 2017;Mpondo et al, 2021;Nicholls et al, 2020). This is because there is a correlation between the public perceptions towards a species and their knowledge of that species (Burns et al, 2021;Fančovičová & Prokop, 2011;Prokop et al, 2008;Silva & Minor, 2017;Sumner et al, 2018;Trip et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations